Hubungan Obesitas Sentral dengan Hitung Jenis Leukosit pada Laki-Laki Dewasa di Lingkungan Universitas Lampung - Khairun Nisa Berawi; Chicy WIdya Morfi; Diva Iole Humaira (Medula, 2020)
Obesity is a condition characterized by excessive accumulation of fat in the body. One form of obesity is central obesity which is characterized by the accumulation of fat, especially in the abdomen, and is more common in men. Central obesity has a stronger correlation with various diseases as a result of chronic inflammatory reactions that occur in adipose tissue. This ongoing inflammatory process will cause changes in various immunological parameters, one of which is leukocyte count. This study aims to determine the relationship between central obesity and leukocyte count in adult obese men. This research uses a cross-sectional approach. 59 study subjects were consisting of 39 central obese men and 20 non-obese central men. Venous blood samples were used in the calculation of differential counts and calculated Manually by microscope. The results showed a significant association between central obesity with neutrophil (p= 0,01), monocyte (p= 0,031) and lymphocyte counts (p= 0,003) but eosinophils and basophils did not have a significant relationship (p= 0,106 and p= 0,166). There is a relationship between central obesity with neutrophil type counts, monocytes, and lymphocytes in adult males with central obesity but eosinophils and basophils have no relationship.